Digital Labor Platforms as a Source of Social Pollution - Marina Chudinovskikh; Alena Fedorova; Ilona Polents; Aleksandr Ovchinnikov (Communications of International Proceedings, 2020)
The article discusses the features of organizing employment through Internet platforms. The authors identify the main employment models, the advantages and disadvantages of working through platforms and the risks of social pollution of labor relations. To identify the main difficulties faced by employees, the ratings of the most popular platforms and services in Russia (Uber, YandexTaxi, YandexFood, Profi, Delivery Club) were studied, the least satisfaction was revealed in such parameters as career growth and relationships with managers. The overall assessment by platform workers does not exceed 2.5 points on a 5-point system, which allows us to conclude that there is a high level of social pollution. Based on the content analysis of the feedback from Delivery Club employees, the problem of illegal fines and deprivation of bonuses was diagnosed. The results of the study led to conclusions about the need to improve the legal regulation of labor relations in sphere of work based on digital platforms.
Keywords: Internet Platforms; Employment; Telework; Social Pollution; Rating; Content Analysis.